PERANAN TANAMAN SEMAK DALAM UPAYA MENGURANGI POLUTAN NOx DAN CO - Nanny Kusminingrum (Direktorat Bina Teknik Jalan dan Jembatan, 2007)
Vegetation in roadway environment consists in general of trees, shrubs and bushes. Bushes are the vegetation type with lowest posture compared to trees and shrubs. On the green path of the roadway environment, vegetation can be grown along the side walk or roadway shoulder, in general with tress. However, by using pot type vegetation, shrubs and bushes can also be grown. The vegetation type for roadway median is according to regulations only allowed for shrubs and bushes.City parks, functioning as breathing path or city lungs can be grown with a combination all tress type of vegetation. The benefits of green open are most important in protecting the living environment all tress type of vegetation. The benefits of green open areas are most important in protecting the living environment in cities against varoius pollutions including air pollution. Bush vegetation is a vegetation type that can be combined with shrubs and trees, in reducing pollution and improving the air quality of the roadway environment. In this case study, the role of bushes is not only investigated from esthetical point of view, but mainly on the improvement of public service for road users and surrounding environment, creating benefits like comfort in environmental health. Result of studies shown that bushes are reducing NOx : (20.49 - 54.42) % and CO : (35.14 - 92.22) % Keywords : Air Pollution, Vehicle, bushes